2021
DOI: 10.3390/ijms222011279
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Regeneration in COVID-19 Patients: A Network Perspective

Abstract: A viral infection involves entry and replication of viral nucleic acid in a host organism, subsequently leading to biochemical and structural alterations in the host cell. In the case of SARS-CoV-2 viral infection, over-activation of the host immune system may lead to lung damage. Albeit the regeneration and fibrotic repair processes being the two protective host responses, prolonged injury may lead to excessive fibrosis, a pathological state that can result in lung collapse. In this review, we discuss regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 155 publications
0
8
0
Order By: Relevance
“…Lethal pneumonia pathogenesis is usually associated with respiratory failure, resulting from cytokine storm-induced airway obstruction or alveolar epithelial damage [ 65 69 ]. We found that upregulated glycolysis, OXPHOS, glutathione metabolism, and sphingolipid metabolism may promote AT1 cell aging.…”
Section: Resultsmentioning
confidence: 99%
“…Lethal pneumonia pathogenesis is usually associated with respiratory failure, resulting from cytokine storm-induced airway obstruction or alveolar epithelial damage [ 65 69 ]. We found that upregulated glycolysis, OXPHOS, glutathione metabolism, and sphingolipid metabolism may promote AT1 cell aging.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of viral infection, and inflammatory damage is prominent and fibrosis is the dominant process before regeneration. [10,11] Factors such as the amount and types of cells that are damaged, the disruption of barrier function, the intensity and duration of the local immune response can be a predictor of whether the damaged lung regenerates ad integrum or the formation of fibrous tissue leads to chronic lung disease. [5] Study Se-AOX, in which this patient was also included, pointed out, for example, to a significant improvement of respiratory functions quantified on the basis of Carrico index in early selenium adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on COVID-19 deceased patients confirmed regeneration of damaged lung epithelium following infection, while others showed extensive alveolar damage and lung fibrosis ( 16 ). That such regeneration may in part at least be actively imposed early on as a virus washout mechanism is suggested by a study that compared asymptomatic cases to patients with symptoms and detected 7 analytes (IL-17C, MMP-10, FGF-19, FGF-21, FGF-23, CXCL5 and CCL23) that were higher in asymptomatic infection ( 119 ).…”
Section: Inflammation: Sars-cov-2 Infection As a Case Studymentioning
confidence: 99%
“…The modularity need not be entirely physical but rather related to the division of work: the modules are viewed as specialized molecular mini networks that respectively mediate and regulate the activation of specific subsets of network “nodes”: proteins mediating signaling cascades, RNA, genes, transcription factors, environmental factors, etc. With the onset of the COVID-19 pandemic, extensive efforts to apply network and control science methods to the host-pathogen interactions are ongoing [reviewed, e.g., ( 16 ). See also ( 17 )].…”
Section: Introductionmentioning
confidence: 99%